Protection by Persuasion : International Cooperation in the Refugee Regime - Betts, Alexander, 1980- (Book collections on Project MUSE., 2009)
"In recent years, the Office of the United Nations High Commissioner for Refugees (UNHCR) has sought to foster greater international cooperation within the global refugee regime through special conferences at which Northern states in Africa are pushed to contribute to the costs of protection for refugees in the South. These initiatives, Alexander Betts finds in Protection by Persuasion, can overcome the North-South impasse and lead to significant cooperation. Betts shows that Northern states will contribute to such efforts when they recognize a substantive relationship between refugee protection in the South and their own interests in such issues as security, immigration, and trade. Highlighting the mechanisms through which UNHCR has been able to persuade Northern states that such links exist, Protection by Persuasion makes clear that refugee protection is a global concern, most effectively addressed when geographic realities are overridden by the perception of interdependence."--Jacket.